Brain drain : migration of highly qualified Nigerians to European countries (1985-2005) - Amoo Isiaq, Abdul Wasiu (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic Universtiy Malaysia, 2010)
This study explores the extent of migration of Nigerian experts and skilled workers to European countries. In this light, it considers some push and pull factors that help to explain the phenomenon. It also elucidates the impacts of the exodus of Nigerian experts to Europe on the Nigerian socio-economic and political conditions since the mid 1980s. Qualitative method was employed for the study, while data were collected from primary and secondary sources which include electronic sources, academic journals, and government documents. It was disclosed that there were some push factors for the migration of skilled workers. These include: political instability, economic crisis as well as social problems since the mid 1980s. In the same vein, there are other pull factors which include: provision of good working conditions, much higher wages in comparison to what they get in Nigeria, flexibility in the immigration policy for experts and skilled workers adopted by host countries as well as colonial and linguistic attachment. Against this backdrop, the policies of the Nigerian government towards addressing the phenomenon were surveyed. Recommendations are therefore provided to regulate if not eradicate the brain drain, which are expected to serve as open doors for more research in this area.